(untitled) (EUROPEAN AND ASIAN LAW REVIEW, 2023)
The fight against corruption, due to its changing forms and methods, must be permanent and comprehensive. Moreover, all levels of society are affected by corruption. The digitalization of administrative procedures makes it possible to increase the efficiency of public administration and ensure the transparency of decisions made. However, it is necessary to assess how the goals and the implementation coincide. The research methodology includes formal dogmatic, comparative legal, historical, as well as statistical and functional methods. Russia has adopted another plan to combat corruption, which is “reinforced” by the introduction of the new Poseidon system, which ensures compliance with anti-corruption requirements by various officials. However, the constant focus on the digitalization of administrative procedures and control activities cannot automatically lead to the elimination of corruption. It only creates the prerequisites. In addition, program documents do not set such goals, even international legal acts. It is proposed to recognize, digitalization has many advantages - like clearness, simplicity and speed of decision making. Indeed, the electronic form of control measures is convenient: there is no need to wait long, or prepare documents, the control body can check everything immediately. Also, digitalization has already shown its effectiveness in reducing petty corruption. However, for example, there is no detailed statistics on the results of appeals against control measures in public records. It is impossible to assess what was appealed, what decisions were made and what problems arose. At the same time, the universal electronic form will not get rid of negative phenomena - there is no single standard for interaction between an administrative body and an individual. The latter will not always be heard. Furthermore, the regulations do not take into account one important aspect: not all individuals have access to the Internet.